Analisis Pengaruh Kualitas Pelayanan, Harga, dan Suasana Toko terhadap Peningkatan Loyalitas Pelanggan pada Toko Snack UD. Bunda Ida - Katherin JR Purba; Aprinawati Aprinawati (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the effect of service quality, price, and store atmosphere on customer loyalty at UD. Bunda Ida Snack Shop. A sample of 170 respondents was obtained using convenience sampling technique. Primary data were collected through questionnaires and analyzed using multiple linear regression via SPSS 24.0. The results of the t-test and F-test showed that the three independent variables had a positive and significant effect on customer loyalty, both partially and simultaneously. The price variable has the most dominant influence. 94.9% of customer loyalty is explained by these three variables, the rest is influenced by other factors.